“Antes que eu perca a cabeça” - Nader, Wladyr (2018)
The present work is the consequence of a long journey and diverse experiences that resulted in the text Antes que eu perca a cabeça, among other things. Composed and overall published in my blog, the Escrita Blog, the text goes back to the last year of the military dictatorship in Brazil. As a dissertation, I present a non-fiction novel composed by short chapters divided in three parts about the year of 1984 that, in Brasil, represented the begining of a democratic process that, afterall, took an additional year to be materialized. The process of composition of the novel comes from many notes and memories that I conserved from my years as a journalist, passing through almost every year of regime. Lastly, the narrative intend to give my testemony to let us not forget what had happened